Establishing the irrefutable statistical standards which ORI and Article III and state courts must apply in determining data validity. A call for impeachment, debarment and Presidential Pardon - Richard M Fleming; Tapan K Chaudhuri; Gordon M Harrington (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
A considerable amount of attention has recently been focused on addressing issues related to data fraud. As this specific example shows, statistical analysis can be used to determine when data fabrication, falsification or plagiarism has occurred. Presented here is an example of statistical data analysis showing how the original data (HI data) set, reported as being fabricated, was in fact statistically shown to be valid/real data; while another set of data (Hansen data) was reported as fabricated and was statistically shown to be falsified and plagiarized from the original HI data. This particular case looked at changes in weight related to a diet study - with implications for its impact on heart disease and cancer-as evidenced by the involvement of Revival Soy and Avon.  This paper should be used not only for scientific publication analysis of data fraud with particular emphasis in Cardiology and Oncology, but it should also set the irrefutable standard for data validity and fraud analysis for ORI and foe all U.S. and International Courts.